Studies of intramolecular Diels–Alder reactions of nitroalkenes for the stereocontrolled synthesis of trans-decalin ring systems - Williams, David R. (2011)
Studies of thermal IMDA cyclizations of (1E,7E)-1-nitro-deca-1,7,9-trienes and (1E,3Z,7E)-1-nitro-deca-1,3,7,9-tetraenes have been examined. Reactions of these nitroalkenes proceed via transition states featuring characteristics of asymmetric stretch asynchronicity and result in stereoselective formation of trans-fused decalin products. A substantial rate acceleration is observed for IMDA cyclizations exemplified by triene 14 due to steric repulsions of substituents in the tethering chain which promote facile stereocontrolled formation of trans-fused 26.